A comparative analysis of Fuzzy AHP and Fuzzy VIKOR methods for prioritization of the risk criteria of an autonomous vehicle system - Mehrparvar, Marmar; Majak, Jüri; Karjust, Kristo (Proceedings of the Estonian Academy of Sciences, 2024)
In the current study, two widely used multi-Âcriteria decisionÂ-making methods, the Fuzzy analytic hierarchy process (AHP) and the Fuzzy VIKOR method, have been implemented to prioritize the criteria of a multiÂ-criteria decisionÂ-making problem. Herein, the case study is an autonomous vehicle, the TalTech iseAuto AV shuttle, developed at TalTech University. The criteria of the present problem are evaluated by experts, and after forming the pairwise matrices, these matrices are aggregated by the maxÂ-min method with the arithmetic mean. Subsequently, in the case of Fuzzy AHP, by calculating the weights and normalizing them, the relative importance of each criterion is obtained, which leads to the ranking of the criteria. Moreover, in the case of the Fuzzy VIKOR method, the aggregated pairwise matrix is weighted and normalized. The ranking obtained from both methods is presented and compared. The advantages and disadvantages of the multiÂ-criteria decisionÂmaking methods Fuzzy AHP and VIKOR, featured for risk analysis of the autonomous vehicle systems, are discussed.